The US Research University – Systemic Limits of a Model - Stephan Bieri; Franz Lehner (Center for Research in Economics, Management and the Arts (CREMA), 2014)
The US research university is a very successful model of higher edudaction and research. We examine its core elements and follow the current discussion on a necessary reform. Focusing on the institutional structure, we review possible causes of shortcomings and frictions. During the last 50 to 60 years the environment of the research university changed. The single institution has become highly dependend on federal and industrial grants and of undergraduates' fees. This process has transformed the internal organization as well as the interaction with important stakeholders. It also had an effect on the relationship between university and faculty. As a result, the scientific production has grown reamarkably but not necessarily the overall competivity. We discuss the systemic challenges that threaten the US university landscape and its contribution to scientific progress and innovation.
Keywords: D12; 330; Research university; US system of higher education; institutional structure